Twelve weeks to change a life : at-risk youth in a fractured state - Greenberg, Max A. (University of California Press, 2019)
"Hailed as a means to transform cultural norms and change lives, violence prevention programs signal a slow-rolling policy revolution that has reached nearly two-thirds of young people in the United States today. Max A. Greenberg takes us inside the booming market for programming and onto the asphalt campuses of Los Angeles where these programs are implemented, many just one hour a week for 12 weeks. He spotlights how these ephemeral programs, built on troves of risk data, are disconnected from the lived experiences of the young people they were created to support. Going beyond the narrow stories told about at-risk youth through data and in policy, Greenberg sketches a vivid portrait of young men and women coming of age and forming relationships in a world of abiding harm and fleeting, fragmented support. At the same time, Greenberg maps the minefield of historical and structural inequalities that program facilitators must navigate to build meaningful connections with the youth they serve. Taken together, these programs shape the stories and politics of a generation and reveal how social policy can go wrong when it ignores the lives of young people"--Provided by publisher.